USING DLC STRATEGY TO IMPROVE THE EIGHTH GRADERS’ WRITING SKILL ON DESCRIPTIVE TEXT AT SMPN 1 SEMBAWA - Syafruddin .; Milawati . (Jurnal Didascein Bahasa, 2018)
The objective of this study is to find out: a) whether or not there was any significant improvement in writing descriptive text between the students who were taught by using DLC strategy and those who were not at the Eight Grade Students of SMPN 1 Sembawa. b) whether or not there was any significant difference in writing achievement between the students who were taught by using DLC strategy and those who were not at the Eight Grade Students of SMPN 1 Sembawa. In this study used a quasi experimental design, there were experimental group and control group. Both of them were given a pre-test and post test (before and after treatment). The population of the study was the entire eighth graders of SMPN 1 Sembawa in Academic Year 2017/2018. In this study, the writer used purposive sampling that consists of 35 students for experimental group and 35 students for control group. To analyze the hypotheses, the data from pre-test and post-test from the experimental and control group were analyzed by using paired sample t-test and independent sample-test. Based on the result of paired t-test with t-obtained < t-table and with the mean of pre-test was 40,32 to 69,85 in post-test, it meant that the students‘ writing skill on descriptive text was significantly improved. Based on the result of independent sample t-test of post-test results of both experimental and control group, the output sig. level 0,05 in two tailed testing with df = 68 and the critical value of t-table = 1,995 since the value of t-obtained 6,999 was higher than the critical value of t-table. It meant that the students‘ writing skill on descriptive text was significantly differenced.Key words: DLC strategy, descriptive text, writing skill.